MODEL PEMBANGKIT DATA CURAH HUJAN: STUDI KASUS STASIUN SIMPANG ALAI KOTA PADANG - Sudiar, Nofi Yendri (Sainstek : Jurnal Sains dan Teknologi, 2015)
The effort on constructing weather data generator to cope with the scarcity of daily rainfall data is becoming essential recently. The objective of the paper is to generate rainfall daily data using stochastic spreadsheet. This technique can generate random values derived from the Gamma distribution which is initiated by the determination of rainfall probabilities, the occurrences on certain days and followed by the generation of rainfall height. The result showed that the rainfall data generator in Padang at period 1976-2005 showed consistent patterns with the observation eventhough simulation on day 180th the value is too high. Based on T-paired test, it showed no statistically significant different between simulation and observation (P-Value=0.000). Thus, the model can be employed as daily rainfall generator that can be further used to support the sustanaibility of agricultural activitiesin and food security in Padang. Key words: the scarcity, Gamma distribution, food security